Observing the fate of tRNA and its modifications by nucleic acid isotope labeling mass spectrometry: NAIL-MS - Heiss, Matthias (RNA Biol, 2017)
RNA in yeast, especially rRNA and tRNA are heavily modified to fulfill their function in protein translation. Using biosynthetic stable isotope labeled internal standards we quantified 12 modified nucleosides in tRNA from S. cerevisiae over 24 hours. We observed different quantities of modified nucleosides in dependence of the growth phase. To elucidate the underlying mechanism of the observed tRNA modification profile adaptation, it is necessary to distinguish the pre-existing tRNA pool and its modifications from newly-synthesized tRNAs. By combination of 2 differentially isotope labeled media we developed NAIL-MS, nucleic acid isotope labeling coupled mass spectrometry. During the yeast growth cycle we observe dilution of pre-existing tRNAs by newly-synthesized tRNAs by the growing number of cells. tRNA was found to be highly stable with only little degradation over the observed period. The method was further used to quantify the levels of modified nucleosides in the original and new tRNA pools. By addition of deuterium-labeled methionine, we could observe the incorporation of new methyl marks on pre-existing tRNAs. For 2′-O-methylcytidine (Cm) we observed a global increase in log phase. We identified extensive 2′-OH-cytidine methylation of the pre-existing tRNAs and the new tRNAs which masks an actual decrease of pre-existing Cm. In contrast, global 5-methylcytidine (m(5)C) levels decreased during growth due to a drop in m(5)C quantities in the original tRNA pool. The NAIL-MS data suggests different mechanisms for tRNA modification adaptation depending on the individual modification observed. With this new tool it is possible to follow the fate of methylated RNAs during growth and potentially compare the impact of different stress conditions on the epitranscriptome.